2015
DOI: 10.3233/thc-150961
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound elastography of the supraspinatus tendon guided by US-MRI virtual navigation

Abstract: Abstract. BACKGROUND: A virtual navigation system (VNS) can combine two imaging modalities for synchronous observation and can be beneficial for diagnosis and treatment. Ultrasound elastography (UE) can distinguish between soft and hard tissues. However, the application of UE to musculoskeletal structures is rare. OBJECTIVE: To evaluate UE of the supraspinatus tendon using ultrasound-magnetic resonance imaging (US-MRI) virtual navigation. METHODS: Sixty patients with an ache in the shoulder were diagnosed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…It is generally agreed that injured Achilles and rotator cuff (RTC) tendons are softer than healthy, asymptomatic tendon tissue ( Table 1 , Table 3 ) [4] , [18] , [21] , [22] , [24] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] . Of the four studies that had compared tendinopathic Achilles tendons with normal tendon using SE, pathological tendons were found to be softer than healthy tendon tissue in three studies ( n = 545 tendon thirds), whereas one study by Sconfienza et al ( n = 48) showed opposite results [4] , [29] , [31] , [40] .…”
Section: Ue Technology and Tendon-specific Basic Knowledgementioning
confidence: 99%
“…It is generally agreed that injured Achilles and rotator cuff (RTC) tendons are softer than healthy, asymptomatic tendon tissue ( Table 1 , Table 3 ) [4] , [18] , [21] , [22] , [24] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] . Of the four studies that had compared tendinopathic Achilles tendons with normal tendon using SE, pathological tendons were found to be softer than healthy tendon tissue in three studies ( n = 545 tendon thirds), whereas one study by Sconfienza et al ( n = 48) showed opposite results [4] , [29] , [31] , [40] .…”
Section: Ue Technology and Tendon-specific Basic Knowledgementioning
confidence: 99%
“…Away from the Achilles tendon, ultrasound elastography has been used to assess supraspinatus muscle and tendon (Figure 3), with tendinosis predominantly being shown as tendon softening, but also regions of increased stiffness, purported to represent reparative fibrosis (Figures 4 and 5)[37-39]. Strain elastography has also been used around the elbow to assess the common extensor tendon.…”
Section: Musculoskeletal Applications Of Elastographymentioning
confidence: 99%